Electrochemistry of nonplanar copper(ii) tetrabutano- and tetrabenzotetraarylporphyrins in nonaqueous media. Issue 94 (14th October 2015) - Ye, Lina; Ou, Zhongping; Fang, Yuanyuan; Xue, Songlin; Song, Yang; Wang, Liping; Wang, Mengli; Kadish, Karl M.
<x xml:space="preserve">Abstract</x> Copper tetrabutano and tetrabenzoporphyrins were synthesized and electrochemically characterized and the substituent effect on spectra, potentials and the HOMO–LUMO gap is discussed.